Integration of mathematics with Fiqh An-Nisa' based on Islamic law and state law - Afda Adin Fauzaydillah; Mohammad Tohir; Muhasshanah Muhasshanah (Fakultas Tarbiyah Universitas Ibrahimy, 2026)
This study aims to describe the integration between mathematics and An-Nisa' Fiqh, especially regarding menstruation and postpartum bleeding for women, based on the perspective of Islamic law and state law. Fiqh An-Nisa' discusses special laws for women, such as menstruation, postpartum bleeding, and Istihadhah, which have direct implications for prayer, fasting, and the implementation of state law. State law also provides regulations on inheritance distribution and women's rights, which can influence the implementation of An-Nisa' Fiqh. Meanwhile, mathematics provides arithmetic, analytical, and logical skills that can facilitate understanding of the law. The research method employs a qualitative analytical approach, incorporating literature studies from Fiqh books, mathematics books, Islamic law references, and state law. The study results indicate that (1) aspects of arithmetic, number lines, mathematical logic, and simple statistics can be applied in calculating the duration of menstruation/postpartum, determining the obligation to make up fasting, and visualizing the menstrual cycle. This integration not only improves religious understanding, but also fosters students' numerical and critical thinking skills; (2) there is potential to integrate mathematics in the application of An-Nisa' Fiqh to achieve more objective justice, both from the perspective of Islamic law and state law; and (3) The integration of mathematics and An-Nisa' Fiqh is relevant to support the madrasah curriculum in Islamic boarding schools that emphasize the development of religious knowledge as well as general knowledge.